2021
DOI: 10.48550/arxiv.2103.08586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hadronic molecules in B decays

Hua-Xing Chen

Abstract: There are eighteen possibly existing D ( * ) D( * ) , D ( * ) K( * ) , and D ( * ) D ( * )− s hadronic molecular states. We construct their corresponding interpolating currents, and calculate their masses and decay constants using QCD sum rules. Based on these results, we calculate their relative production rates in B and B * decays through the current algebra, and calculate their relative branching ratios through the Fierz rearrangement, as summarized in Table III. Our results support the interpretations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 148 publications
(189 reference statements)
2
24
0
Order By: Relevance
“…Concerning the Z cs (4000), Z cs (4220), X(4630) and X(4685) states, there are in the literature interpretations compatible with hadronic molecules [24][25][26][27], compact tetraquark structures [27][28][29][30] and even non-resonance configurations [31]. Besides, the magnetic moments of the Z cs (4000) and Z cs (4220) are calculated by means of light-cone QCD sum rules [32].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the Z cs (4000), Z cs (4220), X(4630) and X(4685) states, there are in the literature interpretations compatible with hadronic molecules [24][25][26][27], compact tetraquark structures [27][28][29][30] and even non-resonance configurations [31]. Besides, the magnetic moments of the Z cs (4000) and Z cs (4220) are calculated by means of light-cone QCD sum rules [32].…”
Section: Introductionmentioning
confidence: 99%
“…They are borrowed from Refs. [48,56], which were obtained in the framework of the the twopoint QCD sum rules. The parameters used in the photon distribution amplitudes are given in Ref.…”
Section: Formalismmentioning
confidence: 99%
“…In Ref. [48], mass, decay constants and production rates of the Z c(s) states were investigated in molecular picture within the QCD sum rules. The obtained results supported that the the Z cs (3985), Z cs (4000) and Z cs (4220) were strange partners of the X(3872), Z c (3900) and Z c (4020), respectively.…”
Section: Formalismmentioning
confidence: 99%
“…Obviously, the masses of Z cs (3985) − and Z cs (4000) + are close, but the decay widths are largely different. These observations immediately stimulated a lot of theoretical studies of the open-strange and hidden-charm tetraquarks [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Some works showed that Z cs (3985) − and Z cs (4000) + are the same states [40,41], while some indicated that they are not the same states [29,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%